Sistem Pembelajaran Berbasis Web (E-Learning) Ma Darussalam Jombang - Anam Ma,ruf; Tjatursari Widiartin; Noven Indra Prasetya (Informatics Engineering Department-UWKS, 2017)
One of the teaching methods are being developed at present is e-learning. E-learning can help teachers in distributing teaching materials without having to be in a class by using the internet, it can maximize the learning time in the classroom is limited.Development of information systems in using the software with method collecting data used in this study is the observation and interview or an interview with the topics that will be taken. To design these applications use structural design methods and manufacturing ie Data flow diagram (DFD) for designing and documenting software systems based on the data flow. In making this software using PHP as the scripting language used to create web pages and MySQL as the database data storage.With e-learning can help the learning process to be optimized. Make it easy for teachers to be able to distribute course material to students in MA Darussalam and also students can easily get the subject matter. Website e-learning can be used as the additional discussion of the media to discuss the subject matter is not yet complete